2021
DOI: 10.1007/s00127-021-02052-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring depressive symptoms and its associates among Bangladeshi older adults amid COVID-19 pandemic: findings from a cross-sectional study

Abstract: Purpose Depression, one of the most common mental disorders, is up-surging worldwide amid the ongoing coronavirus disease 2019 (COVID-19) pandemic, especially among the older population. This study aims to measure prevalent depressive symptoms and its associates among older adults amid the COVID-19 pandemic in Bangladesh. Methods This cross-sectional study was carried out among 1032 older Bangladeshi adults, aged 60 years and above, through telephone interviews in Octob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
68
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(80 citation statements)
references
References 46 publications
(36 reference statements)
9
68
0
3
Order By: Relevance
“…The data showed a greater number of women, with a partner and higher education. Similar results were identified in national 16 and international 17,18 research. In addition, it was identified that 39.7% of the participants had depressive symptoms, similar results were found in a Chinese study (30.8%) 16 in Bangladesh 17 .…”
Section: Discussionsupporting
confidence: 89%
“…The data showed a greater number of women, with a partner and higher education. Similar results were identified in national 16 and international 17,18 research. In addition, it was identified that 39.7% of the participants had depressive symptoms, similar results were found in a Chinese study (30.8%) 16 in Bangladesh 17 .…”
Section: Discussionsupporting
confidence: 89%
“… Chen et al, 2021 ), ( Fang et al, 2021 ), ( Fukase et al, 2021 ), ( Gotlib et al, 2021 ), ( Hammond et al, 2021 ), ( Hao et al, 2021 ), ( Hazarika et al, 2021 ), ( Kibbey et al, 2020 ), ( Liu et al, 2020 ), ( Mistry et al, 2021 ), ( Nishimura et al, 2021 ), ( Robillard et al, 2021 ), ( Sakib et al, 2021 ), ( Suzuki et al, 2021 ), ( Tsang et al, 2021 ), (Y. Wang et al, 2021 ), ( Wong et al, 2021 ), ( Yang et al, 2021 ), ( Young et al, 2021 ) Age 20 7.91 ( An et al, 2021 ), ( Cheema et al, 2021 ), ( Fukase et al, 2021 ), ( Glenister et al, 2021 ), ( Kar et al, 2021 ), ( Kar et al, 2021 ), ( Rashid et al, 2021 ), ( Kim et al, 2021 ), ( Matsumoto et al, 2021 ), ( Nkire et al, 2021 ), ( Robillard et al, 2021 ), ( Rossell et al, 2021 ), (Song et al, 2021), ( Tang et al, 2021 ), ( Turna et al, 2021 ), ( Veldhuis et al, 2021 ), ( Wong et al, 2021 ), ( Yan et al, 2021 ), ( Yang et al, 2021 ), ( Yunus et al, 2020 ) Income disruption/ financial restraints 19 7.51 (Xi an Chen et al, 2021 ), ( Cheng et al, 2021 ), ( Devkota et al, 2021 ), ( Fukase et al, 2021 ), ( ...…”
Section: Resultsmentioning
confidence: 99%
“… Wang et al, 2021 ), ( Wickens et al, 2021 ), ( Wolfson et al, 2021 ), ( Wolfson et al, 2021 ), ( Wong et al, 2021 ), ( Yan et al, 2021 ) Living alone/ isolation 13 5.14 (X. Chen et al, 2021 ), ( Cheng et al, 2021 ), ( Fang et al, 2021 ), ( Kang et al, 2021 ), ( Khoury et al, 2021 ), ( Lan et al, 2021 ), (Y an Liu et al, 2021 ), (Yu an Liu et al, 2021 ), ( Liu et al, 2020 ), ( Mistry et al, 2021 ), ( Nkire et al, 2021 ), ( Veldhuis et al, 2021 ), ( Wang et al, 2021 ) Lack of social support / community support 10 3.95 (Feng et al, 2021), ( Glenister et al, 2021 ), ( Hong et al, 2021 ), ( Kang et al, 2021 ), ( Khoury et al, 2021 ), (Yu an Liu et al, 2021 ), ( Nkire et al, 2021 ), ( Sun et al, 2021 ), ( Wang Liu et al, 2021 ), (H. Wang et al, 2021 ) Geographical location of cohort 10 3.95 ( Ganson et al, 2021 ), ( Glenister et al, 2021 ), ( Guo et al, 2021 ), ( Rashid et al, 2021 ), ( Kim et al, 2021 ), ( Rossell et al, 2021 ), ( Wu et al, 2021a ), ( Yan et al, 2021 ), ( Yasmin et al, 2021 ), (Yunus et al, 2021) Increase workload/ workload changes / working conditions 9 3.56 (J. …”
Section: Resultsmentioning
confidence: 99%
“…Additional efforts should be made to ensure mental health equity among generally disadvantaged people, including racial and ethnic minorities, seniors, homeless people, and those with chronic mental problems [ 18 , 25 , 32 , 35 , 49 ]. Existing free and confidential hotlines can be also extended to provide immediate mental healthcares for vulnerable subpopulations during the pandemic, including children [ 3 , 27 ], pregnant women [ 29 ], the elderly [ 42 ], healthcare workers [ 33 , 54 ], physicians [ 1 ], and young adults [ 9 ]. In addition to such secondary and tertiary prevention for the mental health crisis, primordial and primary prevention strategies should be provided to address such inevitable loneliness and social isolation.…”
Section: Discussionmentioning
confidence: 99%